Design a Successful Program for Voluntary Carbon Footprint Reduction - Xu Hartling (International Journal of Supply Chain Management, 2019)
A voluntary eco-labeling program acts as soft policy instruments to regulate or promote climate change mitigation and carbon footprint reduction. The proper design of an eco-labeling program will likely attract more environmentally cautious companies to participate; it will also demonstrate the authoritativeness and trustfulness to consumers when choosing an eco-labeled product. Ultimately, the environmental consumer behavior will lead to higher market penetration of products with eco-labels. The successful design of an eco-label will: (1) set an appropriate eco-standard accepted by the industry and the participants; (2) offer various degrees of strategic benefits from the participation; (3) ultimately increase the market share of eco-labeling products; and (4) benchmark green (described as more environmentally friendly) quality improvement to the environment, reduce carbon footprint, and benefit the society and human beings.